Expatriates’ adjustment to the host country and the role of cross-cultural in-country training and support - Multisilta, Jenni (My University, 2018)
Purpose The purpose of this thesis is to study the role of cross-cultural, in-country training and support in the expatriates’ adjustment to the host country. The concept of international assignments and the cross-cultural adjustment process related to that are studied. The hardships and challenges of expatriates are identified. Cross-cultural, in-country training and support practices provided by the companies for the expatriates are studied. Methodology/approach An exploratory, mono method qualitative study was conducted in order to answer the research question and the objectives. Deductive approach was used in this study. The data was collected through 5 in-depth, semi-structured interviews of former and current Finnish expatriates and expatriate spouses. Narrative approach was used when analyzing the data from the interviews. Findings The effect of the cross-cultural, in-country training and support on the adjustment depends on multiple factors, like the type of training and expatriate’s previous international experience. Other factors affecting the adjustment are family and spouse, other support networks in the host country, and personality traits, and according to the findings of this study, these factors can partly even substitute cross-cultural training and support. Therefore, the training and support practices should be highly individualized. Flexibility in timing of the training and adaptability of the content is highly suggested. Traditional, standardized cross-cultural training was not found beneficial, if the expatriate had done thorough research about the host country beforehand, had previous experience of international assignments, or had wide support networks in the host country. Value of the study The ideas for cross-cultural training and support for the expatriates might be useful to consider for a company sending their employees abroad or for consulting firms who arrange pre-departure or after arrival orientations.
Keywords: expatriates; cross-cultural training; in-country training; international assignments; cross-cultural adjustment; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|